A reliable and accurate portable device for rapid quantitative estimation of iodine content in different types of edible salt - Kapil Yadav; Rakesh Kumar; Arijit Chakrabarty; Chandrakant S Pandav (Wolters Kluwer Medknow Publications, 2015)
Background: Continuous monitoring of salt iodization to ensure the success of the Universal Salt Iodization (USI) program can be significantly strengthened by the use of a simple, safe, and rapid method of salt iodine estimation. This study assessed the validity of a new portable device, iCheck Iodine developed by the BioAnalyt GmbH to estimate the iodine content in salt. Materials and Methods: Validation of the device was conducted in the laboratory of the South Asia regional office of the International Council for Control of Iodine Deficiency Disorders (ICCIDD). The validity of the device was assessed using device specific indicators, comparison of iCheck Iodine device with the iodometric titration, and comparison between iodine estimation using 1 g and 10 g salt by iCheck Iodine using 116 salt samples procured from various small-, medium-, and large-scale salt processors across India. Results: The intra- and interassay imprecision for 10 parts per million (ppm), 30 ppm, and 50 ppm concentrations of iodized salt were 2.8%, 6.1%, and 3.1%, and 2.4%, 2.2%, and 2.1%, respectively. Interoperator imprecision was 6.2%, 6.3%, and 4.6% for the salt with iodine concentrations of 10 ppm, 30 ppm, and 50 ppm respectively. The correlation coefficient between measurements by the two methods was 0.934 and the correlation coefficient between measurements using 1 g of iodized salt and 10 g of iodized salt by the iCheck Iodine device was 0.983. Conclusions: The iCheck Iodine device is reliable and provides a valid method for the quantitative estimation of the iodine content of iodized salt fortified with potassium iodate in the field setting and in different types of salt.